The efficacy of anti‐IL‐1 targeted therapy in PAPA and PASH syndrome - Chloé Challamel; Céline Girard; Laurent Misery; Assia Touhouche; Marion Fradet; Maëlla Severino‐Freire; Cristina B. Livideanu; Maria P. Konstantinou; Fatma Jendoubi; Carle Paul (JEADV Clinical Practice, 2022)
Abstract Introduction Pyogenic arthritis, pyoderma gangrenosum and acne (PAPA) and pyoderma gangrenosum, acne and hidradenitis suppurativa (PASH) are rare autoinflammatory diseases. Treatment of PAPA and PASH is difficult. Conventional immunosuppressants and tumor necrosis factor (TNF) antagonists fail to control skin lesions in many patients. Materials and Methods We conducted a retrospective observational study of patients treated with interleukin‐1 (IL‐1) antagonists for PAPA or PASH syndrome. We included all PASH and PAPA treated with the IL‐1 antagonists canakinumab and anakinra in Toulouse, Brest and Montpellier, France and report on the patients' response to treatment. Results Four patients were treated with anakinra (one patient) and/or canakinumab (three patients) for 6 months to 10 years. Treatment was associated with sustained improvement of skin lesions: hidradenitis suppurativa in four patients including full resolution of skin lesions in three patients, acne with full resolution in one patient, pyoderma gangrenosum in three patients who experienced full resolution of skin lesions. Anti‐IL‐1 treatment was also associated with full resolution of symptoms associated with spondyloarthritis in one patient. One patient who had been receiving oral corticosteroids for years was able to stop treatment while on IL‐1 antagonist. Discussion IL‐1 antagonists, especially canakinumab, are useful alternatives to treat patients with PAPA or PASH syndrome, especially patients who are non‐responders to conventional treatment and TNF antagonists.